2009
DOI: 10.1088/0031-9155/55/2/009
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of irradiation effects on cancer cells by cross-linked dextran-coated iron oxide (CLIO) nanoparticles

Abstract: We investigated iron oxide nanoparticles with two different surface modifications, dextran coating and cross-linked dextran coating, showing that their different internalization affects their capability to enhance radiation damage to cancer cells. The internalization was monitored with an ultrahigh resolution transmission x-ray microscope (TXM), indicating that the differences in the particle surface charge play an essential role and dominate the particle-cell interaction. We found that dextran-coated iron oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The technical details and performances of our transmission x-ray microscope were reported [37,38,45]. The field of view is 24 μm and the detector is a 2048 × 2048 CCD.…”
Section: Methodsmentioning
confidence: 99%
“…The technical details and performances of our transmission x-ray microscope were reported [37,38,45]. The field of view is 24 μm and the detector is a 2048 × 2048 CCD.…”
Section: Methodsmentioning
confidence: 99%
“…Nanomaterials have been used as radio-sensitizers for cancer treatment, with minimal side effects [123][124][125]. Metal-based nanomaterials can generate photoelectrons to enhance the dose effect of RT and induce cytotoxicity in tumor cells through increased ROS production [123][124][125].…”
Section: Mdscs and Rt Resistancementioning
confidence: 99%
“…Nanomaterials have been used as radio-sensitizers for cancer treatment, with minimal side effects [123][124][125]. Metal-based nanomaterials can generate photoelectrons to enhance the dose effect of RT and induce cytotoxicity in tumor cells through increased ROS production [123][124][125]. In a recent study, Wu et al showed that the combination of RT and a magnetic nanoparticle-based platform with cationic polymer modification induced cytotoxicity in glioma cells and increased the median survival of immunocompetent and athymic glioma mice [126].…”
Section: Mdscs and Rt Resistancementioning
confidence: 99%
“…Despite this, it remains an open question as to whether gold is the optimum material for this purpose. Only a handful of other elements have been investigated for use as radiosensitisers (including platinum, hafnium, gadolinium, and iron (12)(13)(14)(15)(16) ), and there have been no systematic experimental or theoretical comparisons between different materials.…”
Section: Introductionmentioning
confidence: 99%